The Effect of Slice Thickness on the Volume Estimations Performed by Using Cone Beam CT - Seval Bayrak; Omer Said Sezgin; Saadettin Kayıpmaz; Gamze Çan (Cumhuriyet Dental Journal, 2018)
Objective: The purpose of this study is to investigate possible effects of the slice thickness on volume estimations with CBCT.